1981
DOI: 10.1111/j.1365-2559.1981.tb01774.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of veins by carcinoma of rectum: method of detection, histological features and significance

Abstract: Histopathological material from operation specimens of rectal adenocarcinoma was reviewed and invasion of veins identified in 51.9% of 703 cases. The extent of venous invasion, thickness of the walls of invaded veins and various other histological features were examined in detail. By follow-up studies recurrence rates, incidence of distant metastases and corrected 5-year survival rates were obtained; correlation with the histopathological results showed that invasion of extramural and thick-walled veins is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
127
1
3

Year Published

1987
1987
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(135 citation statements)
references
References 15 publications
4
127
1
3
Order By: Relevance
“…Although the number of cases is small, our data indicate that the addition of an elastic fibre stain to staining with H+E triples the rate of detection of intermediate venous invasion, whereas the rate of detection of massive venous invasion decreases. Neither Talbot et al, [10][11][12] Dirschmid et al, 20 Inoue et al, 18 Horn et al, 16 17 nor Minsky and colleagues 14 15 refer to the extent of venous invasion. Our present study cannot indicate whether the extent of venous invasion has an effect on the chances of development of clinically relevant distant metastases; therefore, we cannot state whether the extent of venous invasion should be regarded as an indicator of prognosis and reported routinely.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the number of cases is small, our data indicate that the addition of an elastic fibre stain to staining with H+E triples the rate of detection of intermediate venous invasion, whereas the rate of detection of massive venous invasion decreases. Neither Talbot et al, [10][11][12] Dirschmid et al, 20 Inoue et al, 18 Horn et al, 16 17 nor Minsky and colleagues 14 15 refer to the extent of venous invasion. Our present study cannot indicate whether the extent of venous invasion has an effect on the chances of development of clinically relevant distant metastases; therefore, we cannot state whether the extent of venous invasion should be regarded as an indicator of prognosis and reported routinely.…”
Section: Discussionmentioning
confidence: 99%
“…According to the those authors, Talbot et al, [10][11][12] and Dirschmid et al, 20 extramural venous invasion is predominant in other stages of colorectal cancer also. Conversely, Minsky et al found a predominance of intramural venous invasion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to hematoxylin and eosin staining, we also used Elastica van Gieson stain in all cases. Each parameter was defined as "present" when invasion was identified with certainty, but defined as "absent" when either not observed at all or not observed with certainty (16,17). Lymph node metastasis was defined as "present" only when histologically proven.…”
Section: Cases and Tissuesmentioning
confidence: 99%